2022
DOI: 10.3389/fpsyg.2022.859170
|View full text |Cite
|
Sign up to set email alerts
|

How Does Corporate Social Responsibility Affect Sustainability of Social Enterprises in Korea?

Abstract: Social enterprises (SEs) are a new concept, integrating corporate profitability and social purposes. SEs seek to realize sustainable social values, rather than short-term profits. It is therefore important to study the factors that affect the sustainable management of SEs. Corporate social responsibility (CSR) is known to improve corporate image and performance; it can also promote the sustainable development of companies. Innovation has been described as the driving force behind corporate growth and ultimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…The ESG system can avoid risks by guiding and regulating the microscopic behavior of enterprises and reducing negative events in the enterprise environment and social perspectives. This research demonstrates the relationship between ESG performance and green bond issuance through empirical evidence, helps investors to correctly understand ESG investment, and changes the previous concept that "ESG investment is just a sentimental investment, " so that it can actively incorporate ESG performance into the investment and decision-making process (89).…”
Section: Discussionmentioning
confidence: 73%
“…The ESG system can avoid risks by guiding and regulating the microscopic behavior of enterprises and reducing negative events in the enterprise environment and social perspectives. This research demonstrates the relationship between ESG performance and green bond issuance through empirical evidence, helps investors to correctly understand ESG investment, and changes the previous concept that "ESG investment is just a sentimental investment, " so that it can actively incorporate ESG performance into the investment and decision-making process (89).…”
Section: Discussionmentioning
confidence: 73%
“…Exemplar studies include that of Khare and Joshi (2018) who broadly defined social impact as the value created for beneficiaries, society, and the world, and the study of Bhattarai et al (2019) who described social performance as an organization’s performance in creating social value for its customers. Oduro et al (2022), Shin (2018), Shin and Park (2019), and Qing and Jin (2022) likewise explained SE social performance as the extent to which it creates value, for instance, through community contribution, social service, and job creation. Along the same lines, Osten and Toaldo (2022) viewed social performance as creating value in terms of concern for, or actions toward, the community, whereas Sabella and Eid (2016) conceptualized social value in terms of how an SE captures value from and communicates it back to communities to promote community development.…”
Section: Social Impact As Conceptualized In Prior Workmentioning
confidence: 99%
“…There has also been an increased interest in factors related to strategic marketing. For instance, Qing and Jin (2022) examined CSR as a management strategy for achieving competitive advantage and found evidence of its positive relationship with SEs’ social performance. Another source of competitive advantage is the stakeholder orientation, which generates strategic resources and increases stakeholder salience to management to foster social performance.…”
Section: Antecedents Of the Social Impact Of Sesmentioning
confidence: 99%
“…Moreover, CSR initiatives can facilitate sustainable growth by promoting employment, economic development, social advancement, and profitability [52]. Therefore, organizations should prioritize the use of CSR to enhance their performance and become sustainable entities [53]. The study by [54] reported a positive effect of CSR on social sustainability (see Figure 1).…”
Section: Csr and Social Sustainabilitymentioning
confidence: 99%